Južna železnička magistrala - Dokić, Mirko (Promet - Traffic&Transportation, 2012)
The author first deal with the historical review of the endeavors to have a parallel main West-East railway route of Ljubljana- Karlovac-Doboj-Stalać constructed and discusses the level of completion up to date. The author reiterates the economic and strategic significance of this traffic route providing linkages of our four republics, while apart from its social and economic meaning its traffic- -related significance is of particular importance in view of the fact that it provides longitudinal links to four major transversal railway routes in the direction of the Adriatic coast and the main Belgrade-Niš route. By the constriction of the remaining two sections (Glina-B. Novi and Valjevo-Lipnica) on the stretch of 120 km the system would be completed as a whole.